APPLICATION OF THE MODIFIED MULTIPLE SIMPLEX METHOD IN ELECTRONIC COMMERCE - Мормуль, Микола; Щитов, Дмитро; Романчук, Любов; Щитов, Олександр (SWorldJournal, 2026)
The article investigates the possibility of using a modified multiple simplex method to solve optimization problems in e-commerce. Particular attention is paid to the problems of advertising budget allocation, inventory management and logistics. The propo